Investigation of molecular regulatory control of the cardiac-enrich acetyl-CoA carboxlase - Manga, Nayna (Department of Medicine, 2024)
Collective data gathered from studies of different forms of heart disease indicate a common denominator among them, namely a detrimental change in energy homeostasis. This inference has led to increasing interest in metabolic interventions to treat the diseased myocardium, termed metabolic modulation. However, the underlying molecular mechanisms directing cardiac metabolism and the changes occurring during pathogenesis are poorly understood. The chronic modification of cardiac metabolism is a process known as metabolic remodeling, which is thought to be mediated by changes in gene expression patterns. This thesis focussed on the gene regulatory programmes directing the expression of metabolic genes during metabolic remodelling. The current study was centred on the enzyme acetyl-CoA carboxylase (ACC) which catalyses the carboxylation of acetylCoA to generate malonyl-CoA, a central metabolite in the regulation of fatty acid oxidation (FAO). There are two isoforms of ACC, ACCa. and ACCj3, both of which are present in the heart. The two isoforms differ with respect to structure, subcellular localisation, tissue distribution and kinetic properties. The particular focal point of this work was the transcriptional regulation of cardiac acetyl-CoA carboxylase (ACCj3), the precise regulatory role of this enzyme in the myocardium is unclear but it is thought to play a key role in cardiac FAO. The hypothesis was that the cardiac enriched isoform of ACC (ACCj3) is distinct in its regulatory control of cardiac FAO compared to ACCa and that evaluation of the regulation of ACCj3 should provide further insight into its regulatory role in cardiac metabolic remodelling. A rat model of hypobaric hypoxia was used; rats were subjected to one week of hypobaric hypoxia (11 % ambient 0 2). Morphological and haematological studies, as well as quantitative real-time PCR to assess changes in metabolic gene expression were conducted on heart tissue. Morphometric data and atrial naturetic peptide (ANP) transcript levels indicated that hypoxia- induced right ventricular hypertrophy in experimental animals and a reversion to the foetal gene expression pattern in this ventricle. In both ventricles, there was a co-ordinated downward trend in the transcriptional regulation of several genes involved in mitochondrial fatty acid j3-oxidation (PDK4, UCP3, mCPTl and MCD), transcription of glucose transporters (GLUTI and GLUT4) was not significantly altered. Contrary to our expectations, ACCa. and ACCj3 were similarly regulated in both ventricles, indicating that the expression of these isoforms are under the control of analogous regulatory mechanisms which are activated by a hypoxic rather than a hypertrophic stimulus. Transcript levels of both genes were decreased in the right ventricle (RV) and left ventricle and septum (LVS). This result was unexpected for two reasons, firstly the result suggested that both isoforms perform similar functions. Secondly, ACC transcript levels were regulated in a manner imitating that of genes involved in F AO indicating that in addition to regulating FAO via the synthesis of malonyl-CoA, ACC, particularly ACCj3, which is the predominant isoform in the myocardium, may perform another function. In order to further investigate ACCj3 transcriptional regulation, we isolated a 947 bp fragment in the 5'-flanking region of the rat ACCj3 gene. 5'-Rapid amplification of cDNA ends (5'-RACE) analyses showed that this fragment did not contain the known ACCj3 gene promoter. Sequence analysis of this region showed that it contained several putative promoter elements including TAT A and CAA T boxes as well as response elements for several transcription factors implicated, in the regulation of metabolism. Reporter constructs containing 764 bp, 600 bp and 257 bp of the novel sequence upstream of the translation start site of the gene, namely ACC764.luc, ACC600.luc and ACC257.luc, were synthesised. Transfection experiments using these constructs showed that this region could induce transcription in CV-I fibroblast and H9c2 xii myoblasts. Transcriptional induction was almost three-fold higher in H9c2 myotubes suggesting a role for this region in developmental patterning. Induction of transcription was repressed in experiments with ACC600.luc, but this repression was not evident in experiments involving the other constructs indicating that there is a silencer in the region 600 to 258 bp upstream of the translation start site. Co-transfection experiments using expression vectors for the transcription factors involved in the regulation of metabolic gene expression were conducted. The upstream stimulatory factors (USF), USFl and USF2a showed an induction of transcription and the region involved was narrowed down to a 257 bp fragment containing two consensus cis-elements to which these factors bind. The nuclear receptors, peroxisome proliferator-activated receptor-a (PPARa) and retinoid X receptor-a (RXRa), which are known regulators of cardiac metabolic gene expression also induced transcription from this region. Thus, the 5'-flanking region of the rat ACC~ gene immediately upstream of the initiator ATG is able to drive transcription in vitro and may regulate ACC~ gene expression in response to changes in substrate availability. In summary, the data here presented delineate transcriptional modifications in cardiac metabolic gene expression induced by hypobaric hypoxia. There is a co-ordinate downregulation of genes involved in FAO. ACCa and ACC~ were analagously regulated in response to hypoxia and hypoxia-induced hypertrophy indicating that these isoforms have similar regulatory functions. A novel 764 bp fragment in 5'-flanking region of the rat ACC~ gene which may play a role in the transcription and/or post-transcriptional regulation of this gene in response to nutritional flux was isolated and characterised.